Cover Image, Volume 32, Issue 5. (11th May 2021) - Curila, Karol; Jurak, Pavel; Halamek, Josef; Prinzen, Frits; Waldauf, Petr; Karch, Jakub; Stros, Petr; Plesinger, Filip; Mizner, Jan; Susankova, Marketa; Prochazkova, Radka; Sussenbek, Ondrej; et al.
Abstract : The inside front cover image is based on the Original Article Ventricular activation pattern assessment during right ventricular pacing: Ultra‐high‐frequency ECG study by Karol Curila et al., https://doi.org/10.1111/jce.14985 .